2019
DOI: 10.1021/acsabm.9b00046
|View full text |Cite
|
Sign up to set email alerts
|

Mg- and Mn-MOFs Boost the Antibiotic Activity of Nalidixic Acid

Abstract: The development of metal–organic frameworks (MOFs) enclosing active pharmaceutical ingredients is of considerable interest, as their use in controlled drug release and delivery is very promising. Although nalidixic acid is an antibiotic with a broad spectrum of biological applications, effective mainly against Gram-negative infections, its oral bioavailability is low due to a poor solubility and slow dissolution. Herein, we report new metal–organic frameworks (BioMOFs) comprising nalidixic acid and divalent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 65 publications
0
31
0
1
Order By: Relevance
“…More recently, Mg-and Mn-based MOFs were synthesised using the antibiotic agent nalidixic acid [89]. Nalidixic acid is an antibiotic with high bactericidal and bacteriostatic activity against Gram-negative bacteria, yet its low aqueous solubility leads to poor oral bioavailability [90,91].…”
Section: Apis As Linkers: Nalidixic Acid and Mg-mofmentioning
confidence: 99%
“…More recently, Mg-and Mn-based MOFs were synthesised using the antibiotic agent nalidixic acid [89]. Nalidixic acid is an antibiotic with high bactericidal and bacteriostatic activity against Gram-negative bacteria, yet its low aqueous solubility leads to poor oral bioavailability [90,91].…”
Section: Apis As Linkers: Nalidixic Acid and Mg-mofmentioning
confidence: 99%
“…MOFs with biocompatible composition were reported to be viable drug carriers to overcome some of the problems related to drug delivery [ 9 , 20 , 21 , 22 ]. In particular, MOFs designed using antibiotics as ligands to yield antibiotic coordination frameworks (ACFs) were proposed to improve the antimicrobial activity [ 23 , 24 , 25 ], as well as the physicochemical properties of the antibiotics [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium is an abundant metal in the human body and it is vital in several cellular physiological and biochemical processes, such as signal transduction pathways [38], enzyme cofactor [39] and intercellular contacts [40]. Manganese is essential for bone strength but is also involved in enzymatic reactions such as the detoxification of superoxide free radicals in biological systems [21,41]. Zinc is an important trace metal in human nutrition that is crucial for many physiological functions and is involved in several enzyme actions in biological systems [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination of quinolones to biocompatible metals is of considerable interest from biological and pharmaceutical point of views and it has been shown to be an alternative approach to obtain compounds with improved antimicrobial activity while simultaneously altering their physicochemical characteristics [18,19]. Our group has proven that bio-inspired metal-organic frameworks of nalidixic acid, the first quinolone antibiotic, have increased solubility and bioactivity compared to the free antibiotic [20,21]. Efthimiadou et al studied the antimicrobial activity of several pipemidic acid complexes, as well as their interaction with calf-thymus (CT) DNA with diverse spectroscopic techniques, and showed that the complexes are able to bind to DNA; in all the complexes, a B → A CT DNA transition is detected [22].…”
Section: Introductionmentioning
confidence: 99%